Two FERONIA-Like Receptor Kinases Regulate Apple Fruit Ripening by Modulating Ethylene Production - Jia, Meiru; Du, Ping; Ding, Ning; Zhang, Qing; Xing, Sinian; Wei, Lingzhi; Zhao, Yaoyao; Mao, Wenwen; Li, Jizheng; Li, Bingbing; Jia, Wensuo (Frontiers in Plant Science, 2017)
Ethylene has long been known to be a critical signal controlling the ripening of climacteric fruits; however, the signaling mechanism underlying ethylene production during fruit development is unknown. Here, we report that two FERONIA-like receptor kinases (FERLs) regulate fruit ripening by modulating ethylene production in the climacteric fruit, apple (Malus×domestica). Bioinformatic analysis indicated that the apple genome contains 14 members of the FER family (MdFERL1–17), of these 17 FERLs, MdFERL6 was expressed at the highest level in fruit. Heterologous expression of MdFERL6 or MdFERL1, the apple homolog of Arabidopsis FER, in another climacteric fruit, tomato (Solanum lycopersicum) fruit delayed ripening and suppressed ethylene production. Overexpression and antisense expression of MdFERL6 in apple fruit calli inhibited and promoted ethylene production, respectively. Additionally, virus-induced gene silencing (VIGS) of SlFERL1, the tomato homolog of FER, promoted tomato fruit ripening and ethylene production. Both MdFERL6 and MdFERL1 physically interacted with MdSAMS (S-adenosylmethionine synthase), a key enzyme in the ethylene biosynthesis pathway. MdFERL6 was expressed at high levels during early fruit development, but dramatically declined when fruit ripening commenced, implying that MdFERL6 might limit ethylene production prior to fruit development and the ethylene production burst during fruit ripening. These results indicate that FERLs regulate apple and tomato fruit ripening, shedding light on the molecular mechanisms underlying ripening in climacteric fruit.